Telementoring Demonstration in Craniofacial Surgery With HoloLens, Skype, and Three-Layer Facial Models. Issue 1 (January 2019) - Mitsuno, Daisuke; Hirota, Yuka; Akamatsu, Jun; Kino, Hiromi; Okamoto, Toyoko; Ueda, Koichi
Abstract : Background: Telementoring is the technology for providing surgical instruction from a remote place via a network. To demonstrate the use of telementoring in craniofacial surgery, Skype and a mixed reality device HoloLens were adopted, and 3-layer facial models had been developed. Methods: A resident in hospital A used the model surgery under remote guidance by a mentor surgeon in hospital B 4 times on different dates. The straight-line between hospitals A and B is 250 km. The mentor gave the resident guidance via Skype and HoloLens, communicating by voice, and video of the surgical field, and providing reference data. Results: There was no delay in voice communication and a delay of <0.5 seconds in the video. The resident was able to confirm the main landmarks of the surgical field and to grasp the situation without problems. The mentor could send appropriate instructions by voice, could point out a specific part by telestration function, and could draw lines on the 2-dimentional images pasted on the operator's field of vision. Discussion: With the use of HoloLens, Skype, and the 3-layer models, it was possible to demonstrate telementoring. The risk of personal information leakage due to data interception seems to be very low because its data communication is encrypted with advanced encryption standard. Conclusion: This telementoring system has various advantages and many improvable aspects in the field of craniofacial surgery. Abstract : Supplemental Digital Content is available in the text